Church, state, and public policy : the new shape of the church-state debate - American Enterprise Institute for Public Policy Research; Mechling, Jay (Washington, D.C : American Enterprise Institute for Public Policy Research, 1978)
This book is based upon a conference that set out to look for the 'new shape' of church-state relations. It explores the tension that exists between the church and the state and how it can be resolved.
includes bibliographical footnotes
usc 14/7/17
Loans
Keywords: Church and state; United States